Orbital Shear Stress Regulates Differentiation and Barrier Function of Primary Renal Tubular Epithelial Cells. Issue 6 (November 2018) - Ferrell, Nicholas; Cheng, Jin; Miao, Simeng; Roy, Shuvo; Fissell, William H.
Abstract : Primary cells cultured in vitro gradually lose features characteristic of the in vivo phenotype. Culture techniques that help maintain cell-specific phenotype are advantageous for development of tissue engineered and bioartificial organs. Here we evaluated the phenotype of primary human renal tubular epithelial cells subjected to fluid shear stress by culturing the cells on an orbital shaker. Transepithelial electrical resistance (TEER), cell density, and gene and protein expression of proximal tubule–specific functional markers were measured in cells subjected to orbital shear stress. Cells cultured on an orbital shaker had increased TEER, higher cell density, and enhanced tubular epithelial specific gene and protein expression. This is likely due at least in part to the mechanical stress applied to the apical surface of the cells although other factors including increased nutrient and oxygen delivery and improved mixing could also play a role. These results suggest that orbital shaker culture may be a simple approach to augmenting the differentiated phenotype of cultured renal epithelial cells. Abstract : Supplemental Digital Content is available in the text.